KM initiatives, innovation & GLC performance - A. Rahman, Badruddin; Mohd Shariff, Mohd Noor (2008)
A model of knowledge management initiatives, innovation and performance is developed and tested for the listed Malaysian Government Linked companies (GLC).Data collected from 273 employees representing the three different levels of management is subjected to structural equation modelling analysis.The proposed model fits the data well. Results indicate that employees perceived knowledge management initiatives as important antecedents of innovation in the GLC and innovation in turns result in better organizational performance.